Discovery of a New Species of Telenomus (Hymenoptera: Scelionidae) Parasitic on Eggs of Bombyx mandarina and Bombyx mori (Lepidoptera: Bombycidae) in Japan and Taiwan. Issue 4 (6th August 2018) - Matsuo, Kazunori; Hirose, Yoshimi; Yokoyama, Takeshi; Nakajima, Yumiko; Hsu, Yu-Feng; Banno, Yutaka
Abstract: We reared a Telenomus species from eggs of Bombyx mandarina (Moore) (Lepidoptera: Bombycidae) and Bombyx mori (Linnaeus) (Lepidoptera: Bombycidae) in Japan, and from eggs of B. mandarina in Taiwan. Morphological examination revealed that this Telenomus species is new to science. In this article, we describe it as Telenomus moricolus Matsuo et Hirose, sp. nov. Because B. mandarina is considered to be an ancestor of B. mori, a domestic insect, it is reasonable to assume that B. mandarina is an original host of T. moricolus . This is the second discovery of an egg parasitoid attacking wild and domesticated silkworms, following the first discovery of T. theophilae, a Chinese species. The significance of the discovery of T. moricolus is discussed in relation to examining the effects of host-insect domestication on egg parasitism.